National Security Threats in the Indonesian Border Areas with Timor Leste - Yahya, Yudhi; Widjayanto, Joni; Hendra, Afrizal (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The border area between Indonesia and Timor Leste is an area that is vulnerable to national security threats. This situation is caused by various factors, such as differences in socio-economic conditions, illegal cross-border activities, and the potential for conflict between countries both countries. Some of these problems certainly require the role of the government, institutions and society to be resolved properly. The purpose of this writing is to analyze national security threats in the border area between Indonesia and Timor Leste. This paper uses qualitative methods which can provide a description and description of the phenomenon being studied. The results of this research show that the conditions of the RDTL and NKRI border areas in NTT Province do not yet show an ideal picture. The advice that author can give are to increase cooperation in exchanging intelligence data and joint border security operations; build and modernize border post infrastructure and patrol roads; increasing TNI and Polri personnel stationed in border areas; carry out outreach and empowerment of border communities, encourage ratification of the extradition agreement between Indonesia and Timor Leste and establish cooperation and capacity building assistance for Timor Leste in border control.